Review on Mining High Utility Patterns Decreasing Candidates (International Journal of Engineering and Computer Science, 2016)
Utility mining is a latest development of data mining technology. Among utility mining issues, utility mining with the item set share structure is a hard one as no anti-monotonicity property hold swith the interestingness measure.Prior work son this problem all use a two-phase,candidate generation approach with one exception that is however in efficient and not scalable with big databases.This paper plan sa novel algorithm that find shigh utility patterns in a single phase with out generating candidate